THE IMPORTANCE OF THE CORRECT CLASSIFICATION OF EXPENSES IN TEXTILE ENTERPRISES IN THE CONTEXT OF THE TRANSITION TO INTERNATIONAL STANDARDS - Ismailov Naufal Nadirovich (Modern American Journals, 2025)
This article examines the importance of correctly classifying expenses in the textile industry, as well as the relevance of this topic in the context of the transition to international standards. The study analyzed the current problems of cost accounting in the textile industry of Uzbekistan, the requirements of international financial reporting standards (IFRS), as well as theoretical and practical aspects of effective cost management. It was demonstrated how the correct classification of expenses affects the accuracy of financial statements, the quality of management decisions and the investment attractiveness of the enterprise. The article provides practical recommendations on cost classification using various criteria, such as economic structure, dependence on production volume, and calculation methods. The results of the study show that proper cost systematization plays a key role in increasing the competitiveness of textile companies and their successful entry into the international market.
Keywords: Textile industry, cost classification, international financial reporting Standards (IFRS), management accounting, cost optimization, Activity-Based Costing (ABC), investment attractiveness, economy of Uzbekistan.